The Role of Sex Education in Early Childhood: Introducing Internet Ethics to Prevent Cyberporn - Munisa; Rika Widya; M. Syifa Amin Widigdo; Nurhasanah Bakhtiar (Yayasan Multidimensi Kreatif, 2025)
The rapid development of digital technology brings both positive impacts and risks, particularly for young children who are vulnerable to negative content such as cyberporn. This research aims to determine the level of understanding among young children regarding internet ethics and the role of teachers and parents in preventing exposure to cyberporn content. The study was conducted at PAUD Al-Mukhlisin, Medan Deli, involving 15 children aged 5–6 years, 3 classroom teachers, and 10 parents. The method used was qualitative descriptive with data collection techniques including observation and interviews. The results indicate that children's understanding of internet ethics is still low, and only a small proportion of children are aware of the importance of restricting access to certain content. The role of teachers in introducing digital ethics is still limited, while most parents have not optimally supported their children while using the internet. However, the provision of educational media such as animated videos and activity sheets has proven effective in enhancing children's understanding of wise internet use. This research emphasises the importance of collaboration between teachers and parents in fostering children's digital literacy from an early age to prevent exposure to cyberporn.